Physicochemical Properties of Calcium Phosphate Based Coating on Gutta-Percha Root Canal Filling. (6th May 2015) - Al-Haddad, Afaf; Kutty, Muralithran G.; Abu Kasim, Noor Hayaty; Che Ab Aziz, Zeti Adura
Abstract : Dental Gutta-percha (GP) is a polymer based standard root canal filling material that has been widely used in dentistry. However, it has an inadequate sealing ability and adhesion to root dentin. The aim of this study is to coat GP with a bioactive material to enhance its sealing ability and adhesion to the root sealer and subsequently to the root dentin. The choice of coating method is limited by the nature of GP as it requires a technique that is not governed by high temperatures or uses organic solvents. In this study, biomimetic coating technique using 1.5 Tas-simulated body fluids (SBF) was employed to coat the treated GP cones. The coated samples were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray Diffraction (XRD), and field emission scanning electron microscope (FESEM). The presence of hydroxyl, carbonate, and phosphate groups was detected by FTIR while the formation of hydroxyapatite (HA)/calcium phosphate was confirmed with XRD. FESEM revealed uniform, thin, and crystalline HA calcium phosphate coating. The adhesion of the coating to the GP substrate was assessed with microscratch technique. It was viable with cohesive failure mode. In conclusion, Tas-SBF is able to coat pretreated GP cones with a crystalline apatitic calcium phosphate layer.